Media ecological approach in the context of state and municipal policy in vocational education - Alexandra A. Amelina; Anna Yu. Ilina; Yi Zhang (RUDN Journal of Public Administration, 2025)
This study addresses the integration of media ecological principles into educational policy and practice, particularly within state and municipal initiatives aimed at improving vocational education. Media ecology, as an interdisciplinary approach, examines the effects of media environments on human behavior, culture, and learning processes. The study underscores its significance in fostering media literacy, critical thinking, and the development of creative skills among students. The research highlights the role of state and municipal authorities in promoting media education through innovative programs, teacher training, and partnerships with educational institutions and private organizations. It draws on the example of the “Media Class in Moscow School” project, showcasing how municipal support can enhance the quality of education. The project achieved significant outcomes, including improved student performance in specialized exams, increased participation in pre-professional activities, and a rise in high-achieving students. These results demonstrate the efficacy of collaborative efforts in aligning educational policies with the principles of media ecology. Additionally, the study emphasizes the importance of providing teachers with the necessary professional competencies to implement media ecological practices. By fostering a supportive informational environment, schools can protect students from harmful media influences while leveraging digital tools for educational and professional development. The article concludes that the application of media ecology in vocational education not only enhances student engagement and learning outcomes but also prepares them for active participation in the information society. Strategic collaboration between educators, local authorities, and stakeholders is essential for sustaining these innovations and ensuring the successful integration of media literacy into state and municipal education policies.